Contemporary issues of transport logistics development in Republic of Kazakhstan - Tasmaganbetov, A.B.; Таsmaganbetova S.Zh. (BUKETOV BUSINESS REVIEW, 2018)
The article studies the role of transport potential of the Republic of Kazakhstan in the development of logistics infrastructure in market conditions. The main attention is paid to solving management problems of materials and information flows in logistics. The materials flow of logistics is classified on certain grounds: in relation to the logistics system; the quantitative basis; the specific gravity andthe consistency of the goods. The determined role of the information flow in the logistics system is aimed at achieving the efficient movement of the materials flow. Grouped logistic operations are performed in the process of production with materials resources, as well as operations for processing, transmission and storage of relevant information. The article also defines the role of logistics in the planning, management and control of movements of materials, information and financial resources in different systems. Moreover, the essence and importance of transport logistics are revealed by the authors. Because transport is characterized as the main link between the elements of logistics systems. There are main advantages and disadvantages of different transport modes which are related to the rational organization of the goods movement. The activity of Kazakhstan transport and logistics centers providing logistics services in the railway industry is analyzed. Which allows to propose a number of recommendations to address the problems of transport logistics development in the Republic of Kazakhstan.